Effects of Root Extract of Ruellia tuberosa L. on Kidneys of Diabetic Rats - Anna Safitri; Arie Srihardyastutie; Anna Roosdiana; Aulanni`am Aulanni`am; Eva Nur Laili Octaviana (Journal of Mathematical and Fundamental Sciences, 2019)
The aim of this research was to study the antidiabetic activity of root extract of Ruellia tuberosa L. on rats (Rattus novergicus) induced by multiple low doses of streptozotocin. The parameters investigated were blood glucose levels, protease activities, and the histopathologic profiles of the kidneys. Three groups of rats, i.e. control, diabetic, and treatment, were used. R. tuberosa L. extracts were given orally for treatment at a dose of 250 mg/kg body weight per day for 21 consecutive days. The induced diabetes group treated with root extract of R. tuberosa L. (group III) had 60.3% lower glucose levels (119 mg/dL) compared to the group with induced diabetes only. Moreover, antidiabetic activity of R. tuberosa L extract was evidenced by the 55% lower protease activity in the treatment group compared to the untreated diabetic group. Finally, a positive effect from root extract of R. tuberosa L. was shown from the less damaged renal glomerulus and smaller gap between extracellular matrices and epithelium cells in the histopathologic profiles of the kidneys in the extract treatment group. These results show the potential of root extract of R. tuberosa L. as a natural product anti-diabetic agent.